RI 4421 Investigation Of Muir Inlet Or Nunatak Molybdenum Deposits, Glacier Bay, Southeastern Alaska - R. S. Sanford (The National Institute for Occupational Safety and Health (NIOSH), 1949)
The Muir Inlet or Nunatak molybdenum deposits arc in the Glacier Bay district, Muir Inlet, miles northwest of Juneau. The deposits were examined by Bureau of Mines engineers, and the area was mapped by a field party of the Federal Geological Survey during the summer of 1942. 5/ The following year the Bureau of Mines began developing the deposits. A total of 217 channel samples were taken, and 2 diamond drill holes totaling 256 feet wore drilled. The samples were sent to the' Bureau's laboratories at Rolla, Mo. for beneficiation.